An Analysis of Teachers’ Questioning Strategies During the Classroom Interaction at SMAN 4 Takalar - Nurhidayana Wandasari; Munir Munir; Geminastiti Sakkir (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2023)
This study aimed to find out the teachers’ questioning strategies during the classroom Interaction and the reason why the English teacher used their questioning strategies. The English teachers at SMAN 4 Takalar were the subjects of this study. In this study, the method conducted descriptive-qualitative. The instrument of this study was used observation checklist and interview protocol. Observation and interviews were used to collect data on all activities in the classroom. The results of the study indicate that teachers employed several questioning strategies in the classroom, including rephrasing, simplification, repetition, decomposition, and probing. These strategies were used for various purposes based on the functions associated with each strategy. The reason why teachers used these specific questioning strategies is likely due to the functions associated with each strategy. Teachers may have used rephrasing, simplification, repetition, decomposition, and probing to assess students' comprehension, draw their attention, support their contributions in class, and seek clarification or confirmation. These strategies help teachers gauge student understanding, encourage active participation, and create an inclusive and engaging learning environment.Keywords— Teachers’ questions, questioning strategies, classroom interaction